Iron status and nocturnal oximetry in paediatric sickle cell anaemia patients. (4th April 2011) - L'Esperance, V S; Cox, S E; Makani, J; Soka, D; Prentice, A M; Hill, C M; Kirkham, F J
Abstract : Aim: To test the hypothesis that low iron status in children with Sickle Cell Anaemia (SCA), not receiving regular blood transfusions, is associated with lower nocturnal haemoglobin oxygen saturation (SpO2 ) and more sleep-disordered breathing. Methods: 32 children (16 boys, 50%), homozygous for SCA (HbSS; mean age 8.0 years, range 3.6–15.3 years) underwent motion resistant nocturnal oximetry (Masimo Radical). Iron status was assessed by transferrin saturation and averaged steady state haematology indices from the previous year. Only studies with a minimum of 4 h of artifact-free data were included in the analysis. Analysis software yielded standard measures including: mean and minimum SpO2; δ-12s index and desaturation index of 3% or greater from baseline. Results: 28% (9/32) had low transferrin saturation (<16%) indicating probable iron deficiency, a similar proportion to all SCA patients with data available (25%, N=212/836; unpublished data). There was no association between transferrin saturation and age, sex or nutritional status (body mass index z-score) or history of blood transfusion. There were no statistically significant associations between transferrin saturation and steady state haemoglobin, red cell count, mean cell haemoglobin concentration or mean cell volume in these children. Higher transferrin saturation, but within the normal range (all <55%) and adjusted for age and α-thalassaemia deletion, was associated with lower nocturnal mean SpO2 (p=0.013, r2=0.41). Higher transferrin saturation was also associated with higher δ-12s index, a measure of SpO2 variability (p=0.004, r2=0.23) and with the number of SpO2 dips per hour of more than 3% from baseline (p=0.008, r2=0.19). In addition, iron deficiency (transferrin saturation <16%) was associated with an increase of 2.2% in nocturnal mean SpO2. Conclusions: These data suggest that higher iron availability, assessed by transferrin saturation, is associated with nocturnal chronic and intermittent hypoxia. Whether transferrin saturation is aetiologically related to or simply a marker of the observed haemoglobin oxygen desaturation remains to be determined. The longer term consequences of iron status and haemoglobin oxygen desaturation in SCA warrant further detailed investigation in view of the preliminary clinical evidence of a link with unfavourable clinical course.